Penyuluhan Dampak Negatif Pinjaman Online di Desa Moyo: Membangun Resiliensi Ekonomi Masyarakat terhadap Praktik Rentenir Digital - Hambali, Denny; Sugiarto, Aris; Sriyatun; Fitriani, Nurida; Jibrail, Ahmad; Muhammad Rizqi, Reza (Al-Madani: Jurnal Pengabdian Pada MAsyarakat, 2025)
Technological developments have facilitated access to online lending services (pinjol), but behind this convenience lies many risks, especially for rural communities that have low financial literacy. This service activity was carried out in Moyo Village, Sumbawa Regency, with the aim of increasing community awareness about the dangers of illegal pinjol and building economic resilience against digital loan sharks. Through counseling methods, group discussions, case studies, and simulations, participants were given an understanding of the differences between legal and illegal pinjol, legal and social impacts, and how to manage finances wisely. The evaluation results showed a significant increase in participants' understanding, especially regarding the risks of high interest rates, intimidation, and data misuse. The program also successfully equipped the community with financial management strategies such as saving, budgeting, and avoiding excessive consumption. With this program, it is hoped that the people of Moyo Village can avoid digital debt and be more independent in managing their finances.